Special issue on (bio)statistics and biometrics in the age of the digital revolution - Pescim, Rodrigo; Nakamura, Luiz R. (Brazilian Journal of Biometrics, 2024)
This special issue explores the thematic areas presented at the 67th Reunião da Região Brasileira da Sociedade Internacional de Biometria (RBras) and 20th Simpósio de Estatística Aplicada à Experimentação Agronômica (SEAGRO).